2021
DOI: 10.3389/fbioe.2021.757062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sitagliptin Intermediate by a Multi-Enzymatic Cascade System Using Lipase and Transaminase With Benzylamine as an Amino Donor

Abstract: Herein, we report the development of a multi-enzyme cascade using transaminase (TA), esterase, aldehyde reductase (AHR), and formate dehydrogenase (FDH), using benzylamine as an amino donor to synthesize the industrially important compound sitagliptin intermediate. A panel of 16 TAs was screened using ethyl 3-oxo-4-(2,4,5-trifluorophenyl) butanoate as a substrate (1). Amongst these enzymes, TA from Roseomonas deserti (TARO) was found to be the most suitable, showing the highest activity towards benzylamine (∼7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Furthermore, we tested 3‐OTfBE as a substrate. This ester is used to synthesize precursors of gliptins, namely, β‐amino acids obtained through bienzymatic cascade reactions catalyzed by esterases and transaminases [22, 23] . TR 2 E 2 was shown to efficiently hydrolyze 3‐OTfBE ( k cat : 32.47±1.13 min −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, we tested 3‐OTfBE as a substrate. This ester is used to synthesize precursors of gliptins, namely, β‐amino acids obtained through bienzymatic cascade reactions catalyzed by esterases and transaminases [22, 23] . TR 2 E 2 was shown to efficiently hydrolyze 3‐OTfBE ( k cat : 32.47±1.13 min −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We further revealed that this bioinspired design facilitates the one‐step synthesis of a sitagliptin intermediate, specifically the conversion of 3‐OTfBE into 3‐ATfBA in a single one‐pot reaction (Scheme 2). This β‐amino acid is commonly synthesized through a bienzymatic cascade reaction that involves an esterase and a transaminase or a recombinant Escherichia coli strain coexpressing both enzymes [22, 23, 38] . A series of chiral 3‐substituted cyclo‐hexylamine derivatives, capsaicin analogs and nylon‐6 monomer 6‐aminohexanoic acid, to cite some significant examples, have also been synthesized by combining hydrolases with ωTAs as separate catalytic entities [39–41] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations